Biological activity and bioavailability of supramolecular complexes (pectin-boric acid) in vivo of land plants (emryophytes) - Примаченко, С. В.; Кустовська, А. Д.; Мохнєв, Д. С. (Problems of Environmental Biotechnology, 2018)
The bioactivity and bioactivity of a pectin-boric acid supramolecular complex has been studied plant in vivo. The object of research was used lettuce (Lactuca sativa). Maximum bioactivity and bioavailability of the complex were identified after spraying the plant. Referring to the fact that a high concentration of boron was determined in young leaves, this confirms the vertical and horizontal transport of boron in parts of the plant in growth phase.